Preparation and Quality Analysis of Yacon (Smallanthus sochifolius) Wine - Karki, Samit (Himalayan Journal of Science and Technology, 2024)
Three musts containing 24◦Bx TSS, 3.8 ± 0.1 pH and 100 ppm SO2 were prepared from yacon juice, yacon pulp and yacon syrup and were fermented for 20 days at 26 ± 2◦C temperature using wine yeast. The wines were analyzed for chemical (TSS, acidity, antioxidant activity, total phenolics, alcohol, esters, aldehydes, higher alcohol and methanol) and sensory (color, taste, smell, flavor, mouthfeel and overall) characteristics. No significant difference in TSS was found among the wines (7.60 – 8.33◦Bx). Total and fixed acidities (0.86 and 0.72%, m/v as lactic acid), antioxidant activity (98.83%) and total phenolic (86.5 mg GAE/100 mL) were higher in yacon syrup wine, while alcohol (12.5%, v/v) was higher in yacon juice wine. Total esters, aldehydes and higher alcohol contents of the three wines ranged from 51.0 to 68.8 mg ethyl acetate/L, 0.23 to 0.31 mg acetaldehyde/L and 170 to 220 mg/L respectively. No significant difference in methanol content was found among the wines (11.1 – 13.4 mg/L). Sensory evaluation showed that color and mouth-feel preference scores of wines were not significantly different (p>0.05) while the taste, smell, flavor and overall acceptability scores of yacon juice wine were higher than that of yacon syrup wine. Hence, considering antioxidant activity, methanol content and sensory properties, both yacon juice and syrup could be used as raw materials for the preparation of wine comparable in quality to those of fruit wines.